Development and Implications of Controlling in the Public Sector - Margarita L. Vasyunina; Mikhail E. Kosov; Nataliya S. Shmigol; Inna V. Lipatova; Eli A. Isaev; Irina S. Medina; Natalya A. Guz (Emerging Science Journal, 2023)
Controlling is essential for public organizations to deliver optimal performance. However, the existing literature lacks sufficient knowledge to help organizations implement better strategies to enhance control. Therefore, this study examined the concept of control in the public sector, its impact on organizational efficiency, and a key focus on implementation. This study adopted a mixed approach (qualitative and quantitative) to study control in the public sector. The literature review was used to gather qualitative data, and a survey was conducted among the managers working in Russian public organizations to determine their responses to controlling practices. The results were compared and analyzed to provide implications and recommendations. It was noted through the results that control in public organizations depends on various factors like controlling approaches and tools, organizational culture, the autonomy of management, and functional control of organizations. Each of these aspects contributes positively toward control and improves public organizations’ efficiency. Therefore, these aspects should be the core focus of public organizations to ensure greater control and efficiency. This research targeted this area to bridge the gap and determine the concept of controlling the Russian public sector. However, this research also has a limitation in that it has surveyed only 102 managers from different Russian public organizations. Doi: 10.28991/ESJ-2023-07-01-015 Full Text: PDF